IDENTIFICATION OF CONSTRAINTS AND THE ROLE OF EXTENSION WORKERS IN INNOVATION IN WELTH RICE CULTIVATION IN THE RESPONSE TO CLIMATE CHANGE IN NORTH ACEH DISTRICT - Setia Budi; Eva Wardah; Nopri Yanto (CV. Radja Publika, 2025)
Climate change has affected rice productivity in North Aceh Regency, characterized by rainfall fluctuations, increased temperatures, and disruption of agricultural ecosystems. This study aims to identify obstacles faced by farmers in implementing innovations in rice cultivation and analyze the role of agricultural extension workers in supporting adaptation to climate change. The method used in this study was a survey method with qualitative descriptive analysis of 80 respondents in North Aceh Regency. The results showed that the main obstacles included limited adaptive superior seeds (86.56%), availability of irrigation water (80.63%), and low climate literacy (78.24%). The role of adaptive extension workers was assessed as